Econometric foundations - Mittelhammer, Ron C; Judge, George G; Miller, Douglas J (Cambridge Cambridge University Press, 2001)
The text and accompanying CD-ROM develop step by step a modern approach to econometric problems.It provies the principles and procedures for information processing and recovery from samples of economic data.The text fully provides an operational understan
Keywords: Econometrics